2014
DOI: 10.1111/ahg.12072
|View full text |Cite
|
Sign up to set email alerts
|

ABCC5 Transporter is a Novel Type 2 Diabetes Susceptibility Gene in European and African American Populations

Abstract: Numerous functional studies have implicated PARL in relation to type 2 diabetes (T2D). We hypothesised that conflicting human association studies may be due to neighbouring causal variants being in linkage disequilibrium (LD) with PARL. We conducted a comprehensive candidate gene study of the extended LD genomic region that includes PARL and transporter ABCC5 using three data sets (two European and one African American), in relation to healthy glycaemic variation, visceral fat accumulation and T2D disease. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
(70 reference statements)
1
9
0
Order By: Relevance
“…The most prominent metabolic phenotype of Abcc5 ‐/‐ mice is a decrease in total levels of fat mass. Transcriptional profiling of human subcutaneous adipose tissue by Direk et al showed high levels of ABCC5 gene expression and demonstrated that elevated expression of ABCC5 in subcutaneous adipose tissue confers an increased risk for developing T2D with age in populations of disparate ancestry. The prevalence of T2D was reported to be three times higher in subjects with high ABCC5 expression in subcutaneous adipose tissue compared with those with low expression, and overexpression was most strongly associated with increased visceral white adipose tissue accumulation and reduced peripheral insulin sensitivity in nondiabetic individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent metabolic phenotype of Abcc5 ‐/‐ mice is a decrease in total levels of fat mass. Transcriptional profiling of human subcutaneous adipose tissue by Direk et al showed high levels of ABCC5 gene expression and demonstrated that elevated expression of ABCC5 in subcutaneous adipose tissue confers an increased risk for developing T2D with age in populations of disparate ancestry. The prevalence of T2D was reported to be three times higher in subjects with high ABCC5 expression in subcutaneous adipose tissue compared with those with low expression, and overexpression was most strongly associated with increased visceral white adipose tissue accumulation and reduced peripheral insulin sensitivity in nondiabetic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A genome‐wide association study (GWAS) linked elevated expression of an ATP‐binding cassette transporter, ABCC5 , in subcutaneous adipose tissue to reduced peripheral insulin sensitivity in nondiabetic individuals with associated increased visceral fat accumulation and a threefold increased risk of developing T2D with age . This trend was observed in populations of disparate ancestry.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic distances from these maps accurately capture the genetic architecture of the relevant population and have been successfully used in gene-mapping studies for other common diseases. 8,9 We constructed genetic maps for each of these two populations and then used disease-associated location estimates on these maps as the basis for the precise co-localization and replication in both populations. We also analyzed all 76 previously known T2D loci 3 to obtain refined location estimates on the same genetic maps.…”
Section: Introductionmentioning
confidence: 99%
“…A GWA study predicted that ABCC5 might be the new susceptibility gene for type 2 diabetes in humans 174 through regulation of glucagon-like peptide-1 (GLP-1) secretion as demonstrated in Abcc5 -/- mice. 175 Studies in the past have reported a link between type 2 diabetes and glaucomatous optic nerve damage.…”
Section: Quantitative Trait Loci In Pacgmentioning
confidence: 99%